Social Security: Universal or Selective? - Cohen, Wilbur J.; Friedman, Milton (Washington: American Enterprise Institute for Public Policy Research, 1972)
This publication is the sixth in the fifth series of Rational Debate Seminars sponsored by the American Enterprise Institute on Social Security provision for the aged, the disabled, and the dependent.
Includes bibliographical references.
ne 14/05/2018
Loans
Keywords: Social security; Negative income tax